Hearings on Secondary Schools Basic Skills Act. Hearings before the Subcommittee on Elementary, Secondary, and Vocational Education of the Committee on Education and Labor, House of Representatives Ninety-Eighth Congress Second Session on H.R. 5749. To Provide a Program of Grants to Assist Local Educational Agencies to Improve the Basic Skills of Economically Disadvantaged Secondary School Students, and for Other Purposes. Hearings Held on June 12 and 13, 1984 - Congress of the U.S., Washington, DC. House Committee on Education and Labor; Congress of the U.S., Washington, DC. House Committee on Education and Labor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A record of Congressional hearings on the proposed Secondary Schools Basic Skills Act is contained in this document. Following the text of the bill, which is designed to provide junior high and high schools which have large numbers of economically disadvantaged students with funding for programs of quality basic skills instruction, testimony is offered by legislators, educators, scholars, and public officials. Topics covered include the need for legislation, whether the legislation offered is appropriate, expected outcomes, funding, and possible modifications. (CMG)
Educational level discussed: High Schools.
Educational level discussed: Junior High Schools.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Skills; Economically Disadvantaged; Educational Legislation; Federal Aid; Federal Legislation; Federal Programs; Hearings; High Schools; Junior High Schools; Mathematics Skills; Minority Groups; Reading Skills; Secondary Education; Secondary School Students; Writing Skills; Proposed Legislation; Congress 98th; Legal/Legislative/Regulatory Materials